Model Progam Tablet Tambah Darah sebagai Intervensi Spesifik Pencegahan Anemia Remaja Putri di Kota Jambi : Model Progam Tablet Tambah Darah sebagai Intervensi Spesifik Pencegahan Anemia Remaja Putri di Kota Jambi - Sofiyetti, Sofiyetti; Syafiq, Ahmad; Rusmimpong, Rusmimpong; Putra, Egy Sunanda (Amerta Nutrition, 2026)
Background: Anemia is a significant global health problem among adolescent girls and requires effective prevention strategies. One approach to address this issue is Iron Folic Acid Supplementation (IFAS), also known as iron tablet supplementation (TTD), implemented through school-based programs. However, program success depends on the use of appropriate and integrated strategies within the health and education systems to improve compliance, even without direct supervision. Objectives: This study aimed to identify a school-based empowerment intervention model to improve adherence to IFAS among adolescent girls. Methods: A quasi-experimental design was conducted in two high schools in Jambi City over a three-month period. The study involved 78 female students aged 15–18 years, selected using purposive sampling and divided equally into intervention and control groups. The intervention included scheduling one day per week for collective IFA consumption and establishing peer monitoring teams to assess compliance by counting remaining tablets and recording intake using colored body puzzles. The control group received only baseline information. Hemoglobin, erythrocyte, and hematocrit levels were measured before and after the intervention to evaluate effectiveness, and data were analyzed using the Mann-Whitney test. Results: The results showed significant differences between the two groups. Compliance improved (p-value=0.03), hemoglobin increased (p-value=0.001) from 1.02 g/dL to 13.13 g/dL, erythrocyte rose slightly (p-value=0.004), and hematocrit improved (p-value=0.002). Conclusions: The IFAS model effectively improved compliance and hematological outcomes, indicating its potential to support long-term reproductive health among adolescent girls.